Maternal Death at Maharaj Nakorn Chiang Mai Hospital, the 17 Years Experience - Premjit Charoenweerakul; Kasemsri Srisupundit; Theera Tongsong (The Royal Thai College of Obstetricians and Gynaecologists, 2009)
Objective: To analyze the characteristics, leading causes and trend of maternal deaths at Maharaj Nakorn Chiang Mai Hospital between the 20th and the 21st centuries. Study design: Retrospective descriptive study. Methods: The database of Maternal-Fetal Medicine unit and medical records, between January 1991 and December 2007, were reviewed for maternal death cases, causes of death and the causes were categorized into subgroups. Results: There were 72,952 live births and 50 cases of maternal deaths. The overall maternal mortality ratio (MMR) was 65:100,000 live births. Thirty-four (68%) were referral cases. Between the 20th century (1991-1999) and the 21st century (2000-2007), MMR had been dropped from 67/100 000 live births to 62 /100 000 live births. The direct maternal death was the most common cause of death and the top five leading causes were postpartum hemorrhage (PPH), amniotic fluid embolism, heart diseases, septic abortion and severe pre-eclampsia, respectively. Direct maternal death was decreased (MMR from 46.1 to 33.5%) but indirect maternal death were increased (MMR from 9.6 to 23.9%). Conclusion: The trend of MMR at Maharaj Nakorn Chiang Mai Hospital appeared to be minimal changed during the 17 years period. The direct maternal death tends to be decreased but the indirect maternal death tends to be significantly increased. PPH was the most common cause of death in both centuries.